Selection of proper footwear for people with diabetes and its complications - Strojek, Katarzyna; Karpińska, Anna; Styczyńska, Hanna; Zukow, Walery (Journal of Education, Health and Sport, 2018)
Diabetes, which commonly occurs in society, often contributes to the development of adverse complications in the form of micro and macroangiopathy and neuropathy. Irregularities within these structures are the causes of development of diabetic foot syndrome. The prophylaxis plays a very important role in case of people with diabetes. It is recommended to choose the right, individually designed footwear that will prevent the formation of wounds on the feet. In the period of prevention, hygiene and foot control also play an important role in preventing the development of calluses or the formation of cuts. Among people suffering from diabetes, wounds tend to be difficult to heal, therefore, if the wounds occur, comprehensive treatment should be undertaken. In addition to the standard methods of wound supply, it is necessary to unload this body part. It is recommended to wear unloading footwear or insoles that are specially designed for the patient’s needs. Computer foot diagnostics is helpful in choosing the right footwear, it assesses the distribution of foot pressure on the ground while walking (dynamic test) and standing (static test).